Affect of the unconscious: Visually suppressed angry faces modulate our decisions - Almeida, Jorge (2012)
Emotional and affective processing imposes itself over cognitive processes and modulates our perception of the surrounding environment. In two experiments, we addressed the issue of whether nonconscious processing of affect can take place even under deep states of unawareness, such as those induced by interocular suppression techniques, and can elicit an affective response that can influence our understanding of the surrounding environment. In Experiment 1, participants judged the likeability of an unfamiliar item--a Chinese character--that was preceded by a face expressing a particular emotion (either happy or angry). The face was rendered invisible through an interocular suppression technique (continuous flash suppression; CFS). In Experiment 2, backward masking (BM), a less robust masking technique, was used to render the facial expressions invisible. We found that despite equivalent phenomenological suppression of the visual primes under CFS and BM, different patterns of affective processing were obtained with the two masking techniques. Under BM, nonconscious affective priming was obtained for both happy and angry invisible facial expressions. However, under CFS, nonconscious affective priming was obtained only for angry facial expressions. We discuss an interpretation of this dissociation between affective processing and visual masking techniques in terms of distinct routes from the retina to the amygdala.